Audit and Evaluation of the Online Information System Application at Madrasah Ibtidaiyah Negeri (MIN): Case Study of State Islamic Elementery School - Mansyuri, Umar; Hamdan, Hamdan; Arief, Rahadian; Safaatulloh, Asep; Anindya, Andhika (ARRUS Journal of Engineering and Technology, 2024)
Website-based information systems can be utilized as a means to provide quick and accurate information. One of the madrasas that has utilized a website-based information system is MIN 7 Tangerang, which has achieved numerous accolades. On the school's website, users can obtain information about the madrasa. Due to the abundance of information provided on the website, the madrasa administration must ensure data accuracy by conducting an information system audit. The objective of the information system audit is to assess the audit findings on the website for application refinement and to evaluate the implementation of the information system audit for website maintenance at the madrasa. This research employs a qualitative descriptive method. Data collection is conducted through observation and interviews. The interviewees in this study are the auditees, specifically the administrators of the MIN 7 Tangerang website. The research findings reveal eleven audit findings on the madrasa's website, indicating existing deficiencies that require follow-up audits for further refinement and maintenance of the website. In conclusion, the research aims to ascertain audit findings for website application refinement and to evaluate the implementation of information system audit results for the maintenance of the madrasa's website.